Economic Empowerment through Entrepreneurial Ventures: A Holistic Study of Socio-Economic Transformation and Business Creation - Tienni Mariana Simanjorang; Indriana; Imam Hanafi; Eva Desembrianita; Eva Yuniarti Utami (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2023)
This research study examines the dynamic relationships between entrepreneurial resources, opportunities, government policies, economic empowerment, and socio-economic transformation in the context of entrepreneurial ventures in West Java, Indonesia. Using a quantitative approach, this study employs quantitative analysis through Structural Equation Modeling (SEM) with SMART-PLS 4 to assess these relationships and their implications for economic development. The sample comprised 300 entrepreneurial firms from various sectors, representing micro, small, and medium enterprises. Data collected through a structured questionnaire explored respondents' perceptions regarding entrepreneurial resources, opportunities, government policies, economic empowerment, and socio-economic transformation. The data was analyzed, and the proposed hypotheses were tested using descriptive statistics, reliability analysis, confirmatory factor analysis, and path analysis. The study’s results demonstrate a noteworthy and favorable correlation between entrepreneurial resources, opportunities, government policies, and economic empowerment. Furthermore, it is worth noting that economic empowerment has a significant and good impact on socio economic transformation. The fit index of the structural model suggests a satisfactory alignment between the hypothesized model and the empirical data. The findings highlight the significance of available resources, favorable opportunities, and supporting government policies in facilitating economic empowerment inside entrepreneurial enterprises. Furthermore, the results also underscore the importance of economic empowerment in reducing broader socio-economic changes within the region. This study aims to enhance comprehension of the interplay between entrepreneurship, policy, and socio-economic results in West Java.